Multimodality, Anatomical, and Diffusion-Weighted Fetal Imaging of a Spontaneously Thrombosing Congenital Dural Sinus Malformation - Ebert, Mark; Esenkaya, Asim; Huisman, Thierry A. G. M.; Bienstock, Jessica; Kalayci, Tugce Ozlem; Poretti, Andrea; Tekes, Aylin (Neuropediatrics, 2012)
We report on the conventional and diffusion-weighted (DWI) magnetic resonance imaging (MRI) findings of a partially thrombosed torcular Herophili dural sinus malformation. DWI confirmed the intralesional partial thrombosis/blood clot characterized by restricted diffusion. In addition, focal or global intracerebral complications were excluded by fetal DWI. Our findings suggest that DWI is a valuable adjunct to the standard T1- and T2-weighted fetal MRI sequences.
Keywords: vascular anomaly; fetal; diffusion-weighted imaging; magnetic resonance imaging; intracranial